PEMANFAATAN TEKNOLOGI DALAM MENINGKATKAN PEMAHAMAN POLA PERFORMA BELAJAR SISWA: Indonesia, Inggris - Andrian Riyadi; Muhammad Febri Andriyanto (Journal of Automotive Technology and Education, 2025)
Abstract (Inggris) This study aims to analyze the patterns of students' academic performance based on final semester exam scores, attendance, and task participation using the Principal Component Analysis (PCA) approach and the k-means clustering algorithm. The data used in the study were collected from 50 students and included exam scores, attendance rates, and task participation. The PCA method was employed to reduce the dimensionality of the data, resulting in two principal components (PC1 and PC2) that explained 74.57% of  the  data variability. Subsequently, the  k-means algorithm was applied to cluster students into three groups based on their performance patterns. The clustering results revealed three main clusters: Cluster A (low performance), Cluster B (moderate performance), and Cluster C (high performance). These findings indicate that students' academic performance can be influenced by various factors, including attendance, participation, and scores, highlighting the need for more personalized and adaptive learning approaches tailored to each student's characteristics. Abstrak (Indonesia) Penelitian ini bertujuan untuk menganalisis pola performa akademik siswa berdasarkan nilai ujian akhir semester, kehadiran, dan partisipasi tugas dengan menggunakan pendekatan Principal Component Analysis (PCA) dan algoritma k- means untuk pengklasteran. Data yang digunakan berasal dari 50 siswa dan mencakup nilai, tingkat kehadiran, serta partisipasi dalam tugas. Metode PCA digunakan untuk mereduksi dimensi data, yang menghasilkan dua komponen utama (PC1 dan PC2) yang menjelaskan 74,57% variabilitas data. Selanjutnya, algoritma k- means digunakan untuk mengklaster siswa ke dalam tiga kelompok berdasarkan pola performa mereka. Hasil pengklasteran menunjukkan adanya tiga klaster utama: Klaster A (performa rendah), Klaster B (performa sedang), dan Klaster C (performa tinggi). Temuan ini mengindikasikan bahwa performa akademik siswa dapat dipengaruhi oleh berbagai faktor, termasuk kehadiran, partisipasi, dan nilai, yang memerlukan pendekatan pembelajaran yang lebih personal dan adaptif sesuai dengan karakteristik masing-masing siswa.